The influence of perceived strength of brand origin on willingness to pay more for luxury goods. Issue 6 (November 2018) - Siew, Shir-Way; Minor, Michael; Felix, Reto
Abstract Drawing on dual processing theory (Loewenstein et al. in Decision 2(2):55–81, 2015), this paper investigates how the perceived strength of brand origin (PSBO) influences brand love and the willingness to pay more (WTPM) for luxury brands. Participants for two studies were recruited through the consumer panel of a professional survey service provider (Qualtrics). Mediation analysis based on Hayes' (Behav Res Methods 40(3):879–891, 2013) process macro showed that brand love mediates the influence of PSBO on WTPM. This mediating effect through brand love (a highly emotional route) was substantially stronger than the alternative mediating effect through the quality-related aspects of brand luxuriousness (a more cognitive route of processing). Moderation analysis further showed that status consumption has a negative (i.e., attenuating) effect on the relationship between PSBO and brand love. Specifically, the results suggest that whereas consumers low on status consumption use PSBO as an important cue for how much they love the brand, consumers high on status consumption show relatively high levels of brand love, no matter whether PSBO is low or high. The findings make an important contribution to current research on brand origin and brand love, and provide marketing practitioners with options to manage luxury products more effectively.